Solution of distributive problems with synthesis of radar information fields parameters - Нестеров, А. В. (Proceedings of National Aviation University (archive), 1999)
Considered is the approach to solution of the problems of synthesis of radar and information fields parameters. It is proposed that, as the result of the synthesis, the structure of location of ground radar components should be determined. The optimal location of radar and information system is supposed to be determined by the results of the solution of the distribution problems. Considered are three sets of problems: method of linear programming, method of non-linear programming, method of scanning theory. Described are the distinctive features of each method, their advantages and disadvantages also the groups of determining parameters; an advice is given as to the use of particular approach